Blueprint page: Guide to supporting agricultural Nationally Determined Commitments implementation: Planning tools and roadmap development for Greenhouse Gas mitigation in rice production in Vietnam - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
This guide has been published in November 2019, specifying necessary steps to reduce GHG emission in rice production. The Climate and Clean Air Coalition has developed a blueprint page based on this guideline, making it openly available for research networks and policy makers.